Height growth and biomass partitioning during secondary succession differ among forest light strata and successional guilds in a tropical rainforest - Matsuo, Tomonari; Bongers, Frans; Martínez‐Ramos, Miguel; van der Sande, Masha T.; Poorter, Lourens (Oikos, 2024)
In closed‐canopy systems globally, plants exhibit intense competition for light, prioritizing vertical growth to attain elevated positions within the canopy. Light competition is especially intense in tropical rainforests because of their dense shaded stands, and during forest succession because of concomitant changes in vertical light profiles. We evaluated how the height growth of individual tree differs among forest light strata (canopy, sub‐canopy and understorey) and successional guilds (early, mid‐ and late successional species) during secondary succession in a Mexican rainforest. Fourteen secondary forest stands differing in time since agricultural abandonment (1–25 years) were monitored for seven consecutive years. For each stand and census year we estimated relative light intensity (RLI) for each height and categorized trees into forest light strata: understorey (RLI ≦ 33.3%), sub‐canopy (33.3% ≦ RLI ≦ 66.6%) and canopy (RLI ≧ 66.6%), and into successional guilds based on the literature. We estimated two measures of height growth: absolute height growth (HGabs, cm year−1) calculated as the difference in tree height between two consecutive censuses, and biomass partitioning to height growth (HGbp, in kg kg−1 × 100) calculated as the percentage of total aboveground biomass growth partitioned to height growth. Earlier in succession, trees for all strata had greater HGabs and HGbp, resulting in rapid vertical forest development. HGabs was fastest for canopy trees, followed by sub‐canopy and understorey trees. These differences in HGabs among strata, combined with their inter‐specific variation and continuous recruitment of small individuals, lead to a rapid differentiation in tree sizes and increase stand structural heterogeneity. HGbp was greater for understorey and sub‐canopy trees than for canopy trees, reflecting ontogenetic changes in the light competition strategy from growth to persistence. With succession, both HGabs and HGbp decreased, most strongly for canopy trees, probably because of an increased exposure to drought stress. These successional changes stabilize stand size structure and reduce the rate of development.